Anteseden dan Motivasi Kerja - Eka Kurnia Saputra (JURNAL ILMIAH MANAJEMEN & BISNIS, 2018)
This research examines antecedent and consequent of work motivation. Variables in antecedent are perceived organizational support and job satisfaction, while variables in consequent are job performance and intention to leave. The respondent are 80 employees (civil servants) of Riau Archipelago’s mining and energy agency. The method used in this research is survey method, which uses questionnaire and it is distributed to the respondents.  The result indicates the perceived organizational support positively affects job satisfaction, work motivation positively affects job performance, and there is a  negative affects between work motivation and intention to leave. Job satisfaction is not affecting work motivation, perceived organizational support is not affecting motivation and job performance is not affecting intention to leave.